ORAL REHABILITATION IN PATIENTS WITH MAXILLARY OSTEONECROSIS: A CASE REPORT - Natalia Idashkina; Andrii Horoshko; Tetiana Rasinska (Romanian Society of Oral Rehabilitation, 2020)
Bisphosphonate related osteonecrosis of the jaw is a serious complication that may occur in patients using artisanal narcotic drugs. Frequently treatment was not effective, surgical handles and sometimes a number of operations led to extensive defects and deformities of the jaws while maintaining the pathological process (necrosis) in the bone tissue of the jaws, and repeated interventions is difficult an anatomical as well as sound medical judgment. An 8-yearlong case study demonstrated the use of temporary obturator in patients with maxillary osteonecrosis can help restore the ability to eat and speak, improve oral and nasal hygiene (by mechanically eliminating communication with the maxillary sinus), thereby contributing to a more complete their rehabilitation and positively affecting the quality of life.